An investigation into the psychological wellbeing of staff working with self-harm in forensic settings - Gray, Emma (2024)
The relationship between witnessing or experiencing distressing events and acquiring symptoms of trauma is well established. This thesis is concerned with the psychological wellbeing and trauma symptoms of individuals who work in forensic settings, who are regularly exposed to self-harming behaviours. A range of methods were used to explore this. Following an introduction in Chapter One, Chapter Two contains a systematic review investigating the psychological and emotional responses of staff working in prisons and forensic psychiatric hospitals, who are witness to and/or are exposed to regular self-harming behaviours. The review highlights that across the 10 included studies, staff report different immediate and prolonged emotional and psychological responses to managing self-harming behaviours of those in their care, some of which consistent with trauma responses. Findings from the review suggest that those working in prison settings are more likely to report desensitisation and detachment from emotions than those in secure psychiatric hospitals.